Bewegungen des Inlandeises im Lohja—Seebecken, Südfinnland - G. Glückert (Bulletin of the Geological Society of Finland, 1971)
About 760 glacial striae measurements made on polished bedrock outcrops indicate variations in the direction of the movement of Fennoscandian ice-stream in the lake basin of Lohjanjärvi, South Finland. Three major ice-movements of different ages can be observed in the area. The oldest were westerly (240—290°) and the middle flow direction from NNW (320—350°). The youngest glacial movement advancing from a WNW direction (290—320°) was controlled more strongly by the topography than the others. The great NW—SE, N—S and ENE—WSW orientated depressions in the 59-m-deep basin of Lohjanjärvi represent tectonic fracture lines, and they have in a noticeable degree turned the direction of the ice flow in the basin. The lake is a preglacial depression. Its bedrock was originally formed by strong folding and fracturing of the Svecofennian mountain followed by weathering and hollow formation of gneissose limebearing zones and finally by glacial erosion of several ice ages. Two groups of small rock drumlins are formed in the direction of the main ice flow in plane areas at Vohloinen and Lohjansaari. The so-called »Zungenbecken» formations occur in some deep bays near the town of Lohja.